Cosmopolitan soft skills: self- and social awareness fostering human flourishing - Rósa, Blanka (Adult Education Discourses, 2020)
While globalisation is a multidimensional phenomenon, present educational foci tend to lie not on preparing students for a complex, globalised 21st century, but on preparing students for a 21st-century economic globalisation. In order to advocate a change of consciousness, this present study examined the concept of human flourishing and the skills – referred to as cosmopolitan soft skills – fostering the phenomenon. The theoretical analysis undertaken by the study identified flourishing to be a three-dimensional concept and established that flourishing cannot be fully realised unless an individual is flourishing from a positive-psychological, a moral-political, as well as from a moral-ethical perspective. The empirical analysis eventuated a comprehensive list of skills and competences that contemporary educational institutions aim at equipping their students with for the sake of flourishing. Through an interplay between theory and empirical data, the study resulted in a possible conceptualisation of cosmopolitan soft skills, consisting of the four core skills of attention, acceptance, respect, and responsibility as well as 78 other skills organised into four main categories. Provided the critical realist stance taken, the results are believed to be of a flexible and ever-changing but universal nature that facilitate future research into the educability of cosmopolitan soft skills and the empirical realisation of human flourishing.